A Study on Consumer Perception about Organized Vs Unorganized Retailers at Kanchipuram, Tamil Nadu - Ramanathan, V.; Hari, K. (Indian Journal of Marketing, 2011)
Retailing is the most active and attractive sector. Retailing industry has been present for many years in our country. It is only the recent past that has witnessed so much dynamism in this industry. The international retail store chains have caught the fancy of many travelers abroad; however, the action hitherto is missing from the Indian business scene. The emergence of retailing in India has more to do with the purchasing power of buyers, especially of those who live in the post liberalization period. The retail industry offers increasing economies of scale, with the aid of modern supply and distribution management systems and solutions. The current retailing revolution has provided an impetus from multiple sources. These 'revolutionaries' include many traditional and conventional stores upgrading themselves to modern retailing, companies in competitive environments are entering into the market directly to ensure exclusive assortment for their products and services. Chain stores coming up to meet the needs of the manufacturers, who do not fall into either of the above categories, is also an effect of this. Attractiveness, accessibility and affordability seem to be the key offerings of the retailing chain. Retailing is a kind of business activity, which offers products or services in small quantities to the ultimate consumers, at a place where consumers prefer to buy. Especially, in countries like India, till date, the unorganized retailers play a predominant role in offering products or services of a different product (or) service mix at the convenient location (Kirana Stores or Apana Bazar) with effective selling and buyers' retention strategies. However, due to the recent changes in the field of retailing, and with the entry of big domestic corporations as well as multinational and foreign companies into the field of various retailing ventures (in the form of professionally organized ways with the support of technologies and attractive promotional cum selling programmes), the existing unorganized retailers turn their existing business structure. The perception of consumers about both unorganized and organized retailers keeps on changing dynamically. Most of the time, both organized and unorganized retailers are in a dilemma regarding the perception of consumers and hence, due to the unpredictable nature of the customers, both the type of retailers face difficulty in realigning their business strategies. Because of this kind of issue prevailing in today's retail markets; the researchers selected the present topic for their research purpose.